Calculation of the Trajectory of Cations of Metals in an Aqueous Solution under Electric Field; AIP Conference Proceedings; Vol. 2101 : Isotopes: Technologies, Materials and Application (ITMA-2018) - Shamanin I. V. Igor Vladimirovich; Ushakov I. A. Ivan Alekseevich; Timchenko S. N. Sergey Nikolaevich; Poberezhnikov A. D. Andrey Dmitrievich (2019, 2019)
Title screen